2011
DOI: 10.1021/jp207815k
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Geometry of Cooperative Hydrogen Bonds in p-Substituted Calix[n]- and Thiacalix[n]arenes: A Quantum-Chemical Approach

Abstract: (Thia)calix[n]arenes have been widely applied as molecular platforms and host molecules in supramolecular chemistry due to their high level of preorganization and well-detectable conformational preferences. Here we report on quantum-chemical calculations allowing the conformational analysis of p-substituted calix[4]-, calix[6]-, thiacalix[4]-, and thiacalix[6]arenes. To this effect, ab initio and density functional theory (DFT) calculations with the aid of RHF/3-21G, B3LYP/6-31G, B3LYP/6-31G(d,p), and B3LYP/6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 59 publications
2
7
0
Order By: Relevance
“…As shown, the HBEs in substituted CX[4] hosts are predicted to be nearly 30–33 kJ mol –1 . It should be remarked here that HBE values in S-CX[4] and S-CX[4]- t- Bu due to Novikov and Shapiro are ∼4 times larger owing to bifurcated hydrogen-bonded interactions of phenolate oxygen and charge delocalization subsequent to deprotonation. The CX[4]- t -Bu and CX[4]-NH 2 hosts reveal strong hydrogen-bonding interactions compared to those in CX[4]-CH 2 Cl, CX[4]-NO 2 , and CX[4]-SO 3 H or in S-CX[4].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown, the HBEs in substituted CX[4] hosts are predicted to be nearly 30–33 kJ mol –1 . It should be remarked here that HBE values in S-CX[4] and S-CX[4]- t- Bu due to Novikov and Shapiro are ∼4 times larger owing to bifurcated hydrogen-bonded interactions of phenolate oxygen and charge delocalization subsequent to deprotonation. The CX[4]- t -Bu and CX[4]-NH 2 hosts reveal strong hydrogen-bonding interactions compared to those in CX[4]-CH 2 Cl, CX[4]-NO 2 , and CX[4]-SO 3 H or in S-CX[4].…”
Section: Resultsmentioning
confidence: 99%
“…45 Moreover, Fourier transform IR spectroscopic measurements on CX[n] (n = 4, 6, 8) have shown that cyclic cooperative intramolecular hydrogen bonding is responsible for a stable conformation which is not affected by the presence of bulky substituents. 47 In a very recent work, Novikov and Shapiro 18 have studied the energetics and cooperative hydrogen bonding in para-substituted calix[n]arenes and thiacalix[n]arenes employing quantum chemical and density functional calculations. Intramolecular HBEs in calixarene hosts were calculated in terms of the energy difference between the monoanion and the neutral system and by further computing the energy of phenol relative to its anion, which enables one to elucidate the mechanism of nucleophilic substitution reactions.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, in the case of partially substituted thiacalix [4]arenes, the activating ability of the -OH groups of unsubstituted phenol rings is stronger than that of -OR groups and sulfide bonds, resulting in the substitution at the para positions of the -OH groups. Novikov et al 75 evaluated the conformational analysis of p-substituted (thia)calix [4]arenes and (thia)calix [6]arenes by using ab initio density functional theory (DFT) calculations. The calculated hydrogen bond energies indicated strong cooperative effects of intramolecular hydrogen bonds on the conformational distribution and chemical reactivity pattern of p-substituted derivatives of (thia)calix [4]arenes and (thia)calix [6]arenes.…”
Section: Formylation Of Thiacalixmentioning
confidence: 99%